Advanced exergy analysis on a modified auto-cascade freezer cycle with an ejector. (15th October 2016) - Bai, Tao; Yu, Jianlin; Yan, Gang
Abstract: This paper presents a study on a modified ejector enhanced auto-cascade freezer cycle with conventional thermodynamic and advanced exergy analysis methods. The energetic analysis shows that the modified cycle exhibits better performance than the conventional auto-cascade freezer cycle, and the system COP and volumetric refrigeration capacity could be improved by 19.93% and 28.42%. Furthermore, advanced exergy analysis is adopted to better evaluate the performance of the proposed cycle. The exergy destruction within a system component is split into endogenous/exogenous and unavoidable/avoidable parts in the advanced exergy analysis. The results show that the compressor with the largest avoidable endogenous exergy destruction has highest improvement priority, followed by the condenser, evaporator and ejector, which is different from the conclusion obtained from the conventional exergy analysis. The evaporator/condenser greatly affects the exogenous exergy destruction within the system components, and the compressor has large impact on the exergy destruction within the condenser. Improving the efficiencies of the compressor efficiency and the ejector could effectively reduce the corresponding avoidable endogenous exergy destruction. The exergy destruction within the evaporator almost entirely belongs to the endogenous part, and reducing the temperature difference at the evaporator is the main approach of reducing its exergy destruction. Highlights: A modified ejector enhanced auto-cascade freezer cycle is proposed. Conventional and advanced exergy analyses are performed in this study. Compressor should be firstly improved first, followed by condenser and evaporator. Interactions among the system components are assessed with advanced exergy analysis.